Giant intrinsic spin Hall effect in W3Ta and other A15 superconductors - Derunova, E.; Sun, Y.; Felser, Claudia; Parkin, S. S.P.; Yan, B.; Ali, M. N. (Science Advances, 2019)
The spin Hall effect (SHE) is the conversion of charge current to spin current, and nonmagnetic metals with large SHEs are extremely sought after for spintronic applications, but their rarity has stifled widespread use. Here, we predict and explain the large intrinsic SHE in β-W and the A15 family of superconductors: W3Ta, Ta3Sb, and Cr3Ir having spin Hall conductivities (SHCs) of -2250, -1400, and 1210 (S/cm), respectively. Combining concepts from topological physics with the dependence of the SHE on the spin Berry curvature (SBC) of the electronic bands, we propose a simple strategy to rapidly search for materials with large intrinsic SHEs based on the following ideas: High symmetry combined with heavy atoms gives rise to multiple Dirac-like crossings in the electronic structure; without sufficient symmetry protection, these crossings gap due to spin-orbit coupling; and gapped crossings create large SBC.
CRIS-Team Scopus Importer:2022-04-14